Exploring the early experiences of assisted dying in Aotearoa New Zealand: a qualitative study protocol - Jessica Young; Richard Egan; Ben White; Jackie Robinson; Kate Reid; Tess Moeke-Maxwell; Gary Cheung; Jeanne Snelling; Kate Diesfeld; Aida Dehkhoda; Annabel Ahuriri-Driscoll; Te Hurinui Karaka-Clarke; et al. (BMJ Open)
Introduction Increasing numbers of jurisdictions are legalising assisted dying (AD). Developing research protocols to study the experiences and outcomes of legislation is imperative. AD is a topic that, by nature of its complexity and inherent ethical issues, lends itself to qualitative research. Using the objectives of the statutory framework, this qualitative study aims to provide a robust review of the newly formed AD service in New Zealand and the extent to which it is safe, people-centred, dignity-enhancing, accessible and available equitably to all eligible people.Methods and analysis The research uses an appreciative inquiry design to focus on what is working well, what could be improved, what constitutes the ‘ideal’ and how to enable people to achieve that ideal. We are using online semi-structured interviews and face-to-face focus groups to explore the experiences of key stakeholders: eligible/ineligible service users; eligible/ineligible service users with impairments; families of service users; AD providers; non-providers (providers who object to AD and others who are not directly involved in providing AD but are not opposed in principle); health service leaders; and Māori community members. An estimated 110 participants will be interviewed. We will conduct thematic and regulatory analyses of data.Ethics and dissemination The ethical aspects of this study have been approved by the Northern A Health and Disability Ethics Committee through the full review pathway (2023 EXP 18493). To disseminate the findings, we will draft resources to support interviewee groups, to be developed with feedback from stakeholder meetings. We will submit evidence-based recommendations to inform the government review of the End of Life Choice Act 2019. Findings will be disseminated in peer-reviewed publications, conferences, webinars, media, stakeholder feedback sessions and accessible research briefings.